If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -2(2x + -1) = 6(x + 2) Reorder the terms: 8x + -2(-1 + 2x) = 6(x + 2) 8x + (-1 * -2 + 2x * -2) = 6(x + 2) 8x + (2 + -4x) = 6(x + 2) Reorder the terms: 2 + 8x + -4x = 6(x + 2) Combine like terms: 8x + -4x = 4x 2 + 4x = 6(x + 2) Reorder the terms: 2 + 4x = 6(2 + x) 2 + 4x = (2 * 6 + x * 6) 2 + 4x = (12 + 6x) Solving 2 + 4x = 12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 2 + 4x + -6x = 12 + 6x + -6x Combine like terms: 4x + -6x = -2x 2 + -2x = 12 + 6x + -6x Combine like terms: 6x + -6x = 0 2 + -2x = 12 + 0 2 + -2x = 12 Add '-2' to each side of the equation. 2 + -2 + -2x = 12 + -2 Combine like terms: 2 + -2 = 0 0 + -2x = 12 + -2 -2x = 12 + -2 Combine like terms: 12 + -2 = 10 -2x = 10 Divide each side by '-2'. x = -5 Simplifying x = -5
| 7.25(x-2.9)=6.7 | | x^2-2x-77=3 | | 1.03(1.26)(5-x)=6 | | 3(2-12x)=9(1-4x) | | 11x=7x-44 | | 5+4x-1=x-7+2x | | 4n*n= | | 5x-19+3x-1=180 | | 55-40x=30x | | 405=-9(4y+3) | | (4x^2-5)=(3x^2+7) | | p^2+8p=-7 | | 7x-5=6x+(-4) | | -21-6a+5a=3a-5a | | 5x-40=5x | | 10x=4x-57 | | 8-4x=2x-3-6x | | 4(6x-36)=72 | | 4x+5=25+2x | | 11x-2(3x-7)=19+2x | | (4x-1)=(2x+5) | | 30+5=51 | | -25x-6=-5(5x+7)+29 | | 10x+2+4x=(2+12)x-3+5 | | .25a-2=5 | | 12x-3(3x-6)=18+3x | | x-x(.25)=42000 | | 11(w+2)+14=2 | | 15b-2b=-9 | | 6x-30=7-2x | | 2x+3+6x-1=8x+2 | | -2(4+m)=10 |